2009
DOI: 10.1093/occmed/kqp126
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of employees' early retirement intentions: an 11-year longitudinal study

Abstract: Adverse work- or health-related factors detected in middle age predicted subsequent early retirement intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 14 publications
6
76
2
1
Order By: Relevance
“…These scales were based on previous research on work strain conducted at the Finnish Institute of Occupational Health over several decades (32). Mental work strain was assessed with Likert-type items related to employees' feelings of reluctance towards going to work, staying at work, and their general feelings of apathy (33). The The measure of physical work strain was formed from three scales and contained a total of ten items.…”
Section: Mental and Physical Work Strainmentioning
confidence: 99%
“…These scales were based on previous research on work strain conducted at the Finnish Institute of Occupational Health over several decades (32). Mental work strain was assessed with Likert-type items related to employees' feelings of reluctance towards going to work, staying at work, and their general feelings of apathy (33). The The measure of physical work strain was formed from three scales and contained a total of ten items.…”
Section: Mental and Physical Work Strainmentioning
confidence: 99%
“…On a societal level, in all European countries, greater and prolonged labor-force participation throughout a worker's life is necessary in order to confront the social and economic realities and challenges of an aging society. Workers will need to work until an older age, and those with disabilities will need to be integrated or reintegrated into the workforce (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Multiple factors have impacts on ITL, including sociodemographic factors (e.g., age, occupation and family responsibilities 6) work-related factors (e.g., team climate 5) ), and macroeconomic factors such as local job supply 7) . Job satisfaction is a well-documented predictor of exit intentions across professionals; lower levels of job satisfaction predict intention to leave amongst doctors 8) , municipal workers 9) and nurses 6) . A meta-analysis 3) found that ITL is more predictive of employee turnover than overall job satisfaction, satisfaction with the work itself or organizational commitment.…”
mentioning
confidence: 99%